LID study: Plasma lidocaine levels following airway topicalisation for paediatric microlaryngobronchoscopy (MLB). (15th December 2021) - Doherty, Catherine; Quinn, Natalie; Mistry, Sara; Diacono, Jacques; Walker, Robert; Harrison, Anna; Bateman, Neil; Bruce, Iain
Abstract: Objectives: A dose of 5 mg/kg lidocaine is considered appropriate for paediatric airway topicalisation. Existing literature suggests that younger children are susceptible to toxic lidocaine plasma levels and achieve this at a faster rate. Main outcome measures: The primary outcome of this study was to ascertain peak plasma lidocaine levels after topicalisation for airway endoscopy. Secondary endpoints included: time to peak lidocaine plasma levels, signs of lidocaine toxicity (restricted to ECG changes or seizures when under anaesthesia) and clinical adverse events of laryngospasm, coughing or desaturation during the procedure. Setting: Data were collected prospectively over 18 months at Royal Manchester Children's Hospital. Participants: Children aged 0–8 years undergoing elective diagnostic or therapeutic airway endoscopy were included within the study. Design: Standardised 2% lidocaine was used for airway topicalisation. Dose varied depending upon the practitioner's usual practice. Venous bloodsampling occurred at 5, 10, 15 and 20 min post‐administration and plasma lidocaine levels (ng/ml) were analysed. Results: A significant relationship exists between higher peak plasma levels and ages <18 months ( p = .00973). Strong linear correlation exists between body weight and age for our cohort ( r = .88). Higher peak plasma lidocaine levels occur with total dose volumes between 2 and 3 mls of 2% lidocaine local anaesthetic ( p = .03) compared with <2 ml total dose volumes. Data suggest a potential relationship of lower body weights achieving higher peak plasma levels ( p = .0516). Reduced interquartile variation of peak plasma lidocaine levels exists when lidocaine dosing is <5 mg/kg. Conclusions: Age and total dose volume of topicalised lidocaine have a significant relationship with plasma lidocaine levels. A dose of 5 mg/kg topicalised lidocaine for paediatric airway endoscopy is safe and provides good operating conditions. Lower patient body weights trend towards higher peak lidocaine plasma concentrations and require further investigation.